Quality of care and post-discharge morbidity among children diagnosed with severe malaria in rural Uganda: A prospective cohort study. - Jennifer M Kniss; Georget Kibaba; Emmanuel Baguma; Sujata Bhattarai Chhetri; Cate Hendren; Moses Ntaro; Edgar Mulogo; Samson Karabyo; Ross M Boyce (PLOS Global Public Health)
Pediatric severe malaria is a significant contributor of morbidity and mortality in Uganda. Most information is derived from tertiary referral centers and urban centers. Little is known about routine care or post-discharge outcomes in rural areas. We conducted a longitudinal cohort study of pediatric severe malaria at St. Paul's Level IV Health Center (SPHC) in Kasese, Uganda. We collected demographic, clinical, and laboratory results, and conducted follow-up 14 days post-discharge to assess patient outcomes in the immediate post-discharge period. The initial cohort included 187 children aged 0 to 17 years enrolled between July 9th, 2023 and January 9th, 2024. Almost all (94.7%) participants had a parasitological confirmed malaria diagnosis by rapid diagnostic tests or blood smear. While at SPHC, 95.7% of patients received 3+ doses of intravenous Artesunate, and 92.0% also received oral antimalarials. 62.0% had at least one symptom of severe malaria, with altered consciousness (40.6%) and convulsions (29.9%) the most frequently reported. 26.1% had evidence of severe malarial anemia (Hb <5 g/dl), of whom 93.5% received a blood transfusion. Most (82.2%) patients received care that we assessed as consistent with key elements of WHO management guidelines. We were able to contact 183 of the 187 patient caregivers post-discharge. Caregivers reported that 25.6% of patients were experiencing symptoms related to their hospitalization, with fever (18.5%) and nausea/ not feeding well (10.3%) reported most frequently. Children who experienced altered consciousness during their acute illness had 1.69 times the adjusted risk of reporting symptoms 14-days post-discharge compared to those who did not have altered consciousness (aRR: 1.69, 95% CI: 1.01-2.82). Six deaths were recorded, including three at SPHC and three post-transfer or discharge. Findings suggest that at private health facilities in rural areas, treatment appears to be consistent with guidelines. Future research should investigate high morbidity in the immediate post-discharge period.